On the limitations of predicting the ohmic resistance in a macro-cell in mortar from bulk resistivity measurements. (October 2015) - Hornbostel, K.; Angst, U.M.; Elsener, B.; Larsen, C.K.; Geiker, M.R.
Abstract: An experimental setup was designed to simulate the conditions for chloride-induced macro-cell corrosion, in which small anodes are located in a large network of cathodes. The overall aim of the present study was to assess whether measuring the bulk resistivity of reinforced concrete/mortar can give sufficient information about the resistance between anode and cathode inside a macro-cell. Measurements were executed in mortar specimens with high and low resistivities. Both the resistance in the simulated corrosion cells and the bulk resistivity of the mortar mixtures were determined. A comparison of the results showed no direct correlation. This indicates that the common practice of comparing bulk resistivity with corrosion rate may not be sufficient to characterize the corrosion process of chloride induced macro-cell corrosion.